2020
DOI: 10.1088/1757-899x/833/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Inhibition of Saponin Isolates from Pineapple (Ananas comosus L.) and Candlenut (Aleurites moluccanus L.) against Xanthine Oxidase by In Vitro Assay

Abstract: The exploration of gout treatment agent based on the natural product gains high attention in recent years. Although some current drugs effectively treat gout, fewer unbeneficial effects cannot be avoided. Thus, searching for new alternatives with fewer side effects is needed. This present work was aimed at investigating the potency of saponins in pineapple (Ananas comosus L.) and candlenut (Aleurites moluccanus L.) extract as an inhibitor of xanthine oxidase, an enzyme that responsible for gout disease, by in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Saponin was found in PWCE because it is contained in pineapples. Saponin is a triterpenoid found in the plant and is nontoxic to crustaceans, such as shrimp and crab, but toxic to fish [ 17 ]. The study of Emmanuel and Deborah [ 53 ] reported that the amount of saponin contained in pineapple was 0.41 ± 0.03%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Saponin was found in PWCE because it is contained in pineapples. Saponin is a triterpenoid found in the plant and is nontoxic to crustaceans, such as shrimp and crab, but toxic to fish [ 17 ]. The study of Emmanuel and Deborah [ 53 ] reported that the amount of saponin contained in pineapple was 0.41 ± 0.03%.…”
Section: Resultsmentioning
confidence: 99%
“…The bromelain crude extract from pineapple waste could act on the complicated protein digestibility from plant protein in shrimp feed. In addition, the aqueous crude extract consisted of saponin, which was extracted by dissolving in ethanol [ 17 ]. Furthermore, both saponin and bromelain promote nutrient absorption, digestive capacity, and growth performance and provide positive effects in the shrimp's immune system and its resistance to pathogens [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Amalia et al (2020), it found saponin was contained in pineapple, which saponin is a triterpenoid found in the plant. Saponin is nontoxic with crustaceans such as shrimp and crab, but it is toxic with fish.…”
Section: Resultsmentioning
confidence: 99%
“…Saponin was found in pineapple peel extracted by dissolved in ethanol and presented the maximum zone of inhibition against all the test pathogens. This guarantees that pineapple can be used as an antimicrobial agent to protect from selected plant and animal pathogens (Amalia et al, 2020). Furthermore, the active antimicrobial compounds in Ananas comosus L. Merr include saponin and bromelain, which work as antimicrobial through membranolytic properties (Zharfan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%